The Juridical Implications for the Implementation of Therapeutic Agreements Between Hospitals and Patients in the Concept of Legal Certainty - Ginsyah, Ginsyah (TABELLIUS: Journal of Law, 2024)
A doctor is someone who is an expert in disease and treatment and can provide health services to patients. For this reason, patients can contact doctors through medical centers, hospitals and independent practice doctors. In health services between doctors and patients, there is an oral agreement called a therapeutic agreement as a source of legal relations and in writing it regulates in detail and systematically the legal relationship that arises between doctors and patients in therapeutic agreements, the implementation of therapeutic agreements between independent practicing doctors and patients, and responsibilities. the doctor's law against the patient in the implementation of the therapeutic agreement. This research is sociological juridical legal research which is supported by empirical research with descriptive research type. The problem approach used is a qualitative approach. The results of the research and discussion show that the legal relationship between independent practicing doctors and patients is a contractual relationship which in the field of health services is known as a therapeutic agreement between the patient and the hospital. A therapeutic agreement is an agreement to perform certain services (Article 1601 of the Civil Code) and is a type of inspanningverbintenis agreement. namely an agreement based on the doctor's maximum efforts to cure the patient's illness. This relationship is binding because there are rights and obligations of the doctor and patient which are realized in the implementation of the therapeutic agreement. The therapeutic agreement begins when the patient comes to the doctor's office. The patient can be held responsible for the doctor's actions that cause harm to the patient. This liability can be in the form of responsibility due to breach of contract or responsibility due to unlawful acts.